Sumbangan Pemikiran Ibn Rushd (M. 595/1198) dalam Muamalah: Analisis Terhadap Akad Al-Mudarabah dalam Bidayah al-Mujtahid wa Nihayah al-Muqtasid - Borhan, Joni Tamkin; Sa’ari, Che Zarrina (Jurnal Usuluddin, 2007)
This article analyses the thought of Ibn Rushd, a great faqih and thinker of Andalusia in Islamic transactions with special reference to the doctrine of al-mudarabah as found in his Kitab Bidayah al-Mujtahid wa Nihayah al-Muqtasid. His analysis in al-Mudarabah (al-Qirad) contract is still relevant to the contemporary practice of Malaysian Islamic banking and finance in particular in the rest of the world in general.